The Influence of Parental Involvement and Education Policy on Student Achievement in High Schools in NongChok District, Bangkok, Thailand - Saralee Yosai (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2016)
The purpose of this research is to study the influence of parental involvement in education related activities on student achievement in high schools in NongChok District, Bangkok, Thailand. To compare the influence that  parental involvement has  on  student achievement as well as  analyze the joint  influence of parental involvement and education policy on  student achievement,  parents are categorized in accordance with demographic characteristics. The population in the comprised  parents who have  children that are currently studying in  public high schools in NongChok district, Bangkok, Thailand. A non-random sampling method was used in determining the sample of respondents used in the survey.  The calculated sample size was 210 respondents. Data were collected using  structured questionnaire which had 0.88  reliability. Determining demographic characteristics was based on descriptive statistics (percentage, mean, and Standard Deviation; while  One-way ANOVA, and Multiple Linear Regression analysis techniques were used to analyze the data. Study results indicated that  60.5 percent of respondents were married mothers (79.5 percent), had  high school education attainment or equivalent to (51.4 percent), worked  as employees (43.8 percent), earned below or equivalent to  150,000 Baht per year (44.3 percent), and worked less than or equal to 8 hours per day (71.9 percent). Testing of  hypotheses showed that the involvement of parents  in students’ education  of parents takes various forms;  type of the parents  had a statistically significant influence on  students’ achievement at 0.01 level. The results of the multiple linear regression analysis indicated that education policy had significantly influence on  students’ achievement at 0.01 level, while  parental involvement  did not show  statistically significant relationship with  students’ achievement.